'Liberal intellectuals'' narration of the justice and development party in Turkey†. (2nd July 2016) - Ersoy, Duygu; Üstüner, Fahriye
ABSTRACT: This article examines the relationship between a specific group of intellectuals and political power in recent Turkish political history. This group of 'liberal intellectuals' demonstrated constant support for the conservative Justice and Development Party (AKP) governments in the 2002–2010 period, although after 2010, some of these former staunch supporters became fierce critics of the party. The changing circumstances of this relationship shows that a sense of distinction determines the manner in which 'liberal intellectuals' present the AKP, being based on their potential emergence as guides and actors in the 'New Turkey.' This study aims to contextualize and identify the definitive moments in the relationship between this body of 'liberal intellectuals' and the AKP in the 2002–2015 period by examining their narrative directed towards the party in power.